TELEOST OTOLITHS FROM THE AQUITANIAN (EARLY MIOCENE) OF THE FELLI SECTION IN GREECE: THE ROOTS OF THE MEDITERRANEAN GOBY STOCK (GOBIIDAE, GOBIIFORMES) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2021)
Fish otoliths have been obtained from the early Miocene (Aquitanian) Pentalofos Formation of the Mesohellenic Basin in northern Greece. These specimens represent the earliest Miocene shallow marine otolith records from the Mediterranean. Here, we describe the goby otoliths of the assemblage, which are the most common group at this location. They represent the earliest recognized species of two of the three main extant Atlantic-Mediterranean goby groups, the Pomatoschistus lineage and the Aphia lineage. The taxa are interpreted as being phylogenetically positioned near the base of their respective lineages. The new taxa described are Hellenigobius praeschismatus n. gen. et n. sp. and Plesiogobius felliensis n. gen. et n. sp. A third species is tentatively related to Nematogobius in open nomenclature.
Keywords: Early Miocene; Greece; otoliths; sand gobies; Hellenigobius n. gen.; Plesiogobius n. gen.